Endoscopic Endonasal Approach for Clival Chordomas in Elderly Patients: Clinical Characteristics, Patient Outcome, and Recurrence Rate - Zoli, Matteo; Carretta, Alessandro; Rustici, Arianna; Guaraldi, Federica; Gori, Davide; Cavicchi, Riccardo; Sollini, Giacomo; Asioli, Sofia; Faustini-Fustini, Marco; Pasquini, Ernesto; Mazzatenta, Diego (Journal of Neurological Surgery Part B: Skull Base, 2023)
Introduction The endoscopic endonasal route has demonstrated to be the approach of choice for a large majority of clival chordomas (CCs). However, its results in elderly patients are under-evaluated in the literature. The aim of this study is to assess the surgical outcome for these patients, determining the factors associated with a larger tumor resection in this population.Materials and Methods Our institutional database of CC has been retrospectively reviewed, to identify all cases over 65 years old, operated through an endoscopic endonasal approach (EEA). Preoperative clinical and radiological features were considered, as well as surgical results, morbidity, and patients' outcome at follow-up.Results Out of our series of 143 endoscopic surgical procedures for CC, 34 (23.8%) were in patients older than 65 and 10 in older than 75 (7.0%). Gross tumor removal was achieved in 22 cases (64.7%). Complications consisted of 2 (5.9%) postoperative cerebrospinal leaks, 1 (2.9%) meningitis, 1 (2.9%) permanent cranial nerve VI palsy, 1 (2.9%) pneumonia, and 2 (5.9%) urinary infections. In 39.1% of cases, the preoperative ophthalmoplegia improved or resolved. Twenty-seven patients (79.4%) underwent radiation therapy. At follow-up (37.7 ± 44.9 months), 13 patients (38.2%) showed a recurrence/progression and 13 (38.3%) deceased.Conclusion EEA can be a useful approach in elderlies, balancing the large tumor removal with an acceptable morbidity rate, even if higher than that for general CC population. However, patient selection remains crucial. A multidisciplinary evaluation is important to assess not only their medical conditions, but also their social and familiar conditions.
Keywords: chordomas; endoscopic endonasal approach; clivus; skull base; elderly; radiation therapy; outcome; complications; recurrences